Alteration of lipid peroxidation and antioxidant enzymes in young Malaysian IDDM patients - Indran, M.; Pendek, Rokiah; Chan, Siew Pheng; Kuppusamy, Umah Rani (Malaysian Medical Association, 2004)
The present study was designed to explore the relationship between lipid peroxidation and antioxidant enzymes in young Malaysian insulin dependant diabetes mellitus (IDDM) patients. Indicative parameters of lipid peroxidation, activities of antioxidant enzymes and diabetes parameters were evaluated in single blood samples from 30 young type 1 diabetic patients and 30 healthy control subjects. Antioxidant enzymes namely superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GPx) were significantly decreased while plasma malondialdehyde (MDA), an indicator for lipid peroxidation was significantly increased in IDDM patients compared to control subjects. Positive correlations between HbA1c and MDA; fasting blood glucose (FBG) and MDA and negative correlations between HbA1c and SOD; MDA and SOD were observed in these patients. No significant correlation existed between HbA1c and fasting blood glucose, GPx or CAT in the diabetic patients. The strong correlations found between lipid peroxidation, antioxidant enzymes and diabetes parameters confirms the existence of oxidative stress in our IDDM patients.